Anders Norberg m.fl.: Tvåkammarriksdagen 1867-1970. Ledamöter och valkretsar, Band 3. Blekinge län, Kristianstads Län, Malmöhus Län. (Sveriges Riksdag og Almqvist & Wiksell, 1986). 316 s. - Elklit, Jørgen (Historie/Jyske Samlinger, 1989)
-